Environmental Factors Affecting Brook Trout Occurrence in Headwater Stream Segments. Issue 2 (11th March 2015) - Kanno, Yoichiro; Letcher, Benjamin H.; Rosner, Ana L.; O'Neil, Kyle P.; Nislow, Keith H.
Abstract: We analyzed the associations of catchment‐scale and riparian‐scale environmental factors with occurrence of Brook Trout Salvelinus fontinalis in Connecticut headwater stream segments with catchment areas of <15 km 2 . A hierarchical Bayesian approach was applied to a statewide stream survey data set, in which Brook Trout detection probability was incorporated and statistical significance of environmental covariates was based on 95% credible intervals of estimated coefficients that did not overlap a value of zero. Forested land at the catchment scale was the most important covariate affecting Brook Trout occurrence; i.e., heavily forested catchments with corresponding low levels of developed and impervious land area were more likely to be occupied by Brook Trout. Coarse surficial geology (an indicator of groundwater potential) and stream slope had significantly positive effects on occurrence, whereas herbaceous plant cover and wetland and open water area had significantly negative effects. Catchment‐scale and riparian‐scale covariates were highly correlated in many instances, and no riparian‐scale covariate was retained in the final model. Detection probability of Brook Trout at the stream‐segment scale was high (mean, 0.85). Our model had a high predictive ability, and the mean value of receiver operating characteristic area under the curve was 0.80 across 100 leave‐some‐out iterations. The fine spatial grain of this study identified patches of suitable stream habitat for Brook Trout in Connecticut, particularly in the northwestern part. Our analysis revealed a more optimistic status of Brook Trout in Connecticut than did a coarser‐grained analysis across the USA. Received May 13, 2014; accepted November 15, 2014